2017
DOI: 10.1007/s11696-017-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of free and bound 3-monochloropropane-1,2-diol in fat-rich cereal model systems: the impact of flour composition

Abstract: The formation of 3-monochloropropano-1,2-diol (3-MCPD) and its esters in seven fat-rich cereal food model systems was investigated. The models, consisting of triolein, various cereal or pseudocereal flours (buckwheat, corn, millet, oat, rice, wheat, and starch), sugar, NaCl and water, were subjected to thermal processing for 10 min at 200°C and then analysed in terms of the formation of the contaminants. The highest free 3-MCPD level was reached for the model with buckwheat flour (90.7 lg kg -1 ), and the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Sadowsha-Rociek et al . reported that the presence of zinc-containing compounds induced the formation of free 3-MCPD, and our study suggested that metallic zinc can favor the formation of the esterified form of this contaminant.…”
Section: Resultssupporting
confidence: 68%
“…Sadowsha-Rociek et al . reported that the presence of zinc-containing compounds induced the formation of free 3-MCPD, and our study suggested that metallic zinc can favor the formation of the esterified form of this contaminant.…”
Section: Resultssupporting
confidence: 68%
“…First, a higher fat content provided reaction backbones (partial acylglycerol) to form 3-MCPD esters. Secondly, lower pH values provided an acidic condition can catalyse the reaction between lipids structure and chloride ions (Anna Sadowska-Rociek, Cieślik and Florkiewicz, 2017 ). Sodium chloride in the recipe …”
Section: Introductionmentioning
confidence: 99%
“…All dough ingredients were also analysed for 3-MCPDE and GE levels. The extraction and determination of fat was performed using CO 2 in critical phase, according to the procedure formerly developed and validated [ 20 ]. The extracted fat was spiked with 270 μL of PP-3-MCPD-d 5 and P-Gly-d 5 , used as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…The extracted fat was spiked with 270 μL of PP-3-MCPD-d 5 and P-Gly-d 5 , used as internal standards. Further steps were performed according to the procedures described previously [ 20 ].…”
Section: Methodsmentioning
confidence: 99%